Secondary Hyperparathyroidism With "Superscan-Like" Hypermetabolic FDG PET/CT Pattern. (November 2015) - Grellier, Jean-Francois; Lussato, David; Queneau, Mathieu; Guernou, Mohamed; Songy, Bernard
<x xml:space="preserve">Abstract</x> Abstract A 26-year-old man with chronic terminal renal insufficiency under dialysis was referred in our institution for a checkup before kidney transplantation to ensure the absence of malignant neoplasm. The patient had a biological secondary hyperparathyroidism with highly elevated serum parathormon, and treatment with parathyroid surgery was planned before the kidney transplant. Whole-body FDG PET/CT showed no apparent malignant neoplasm, but increased metabolism of the 4 parathyroid gland and the other pitfalls of advanced secondary hyperparathyroidism on chronic renal insufficiency: pseudotumoral calcification in soft tissues, diffuse hypermetabolic bone dystrophy, and osteolytic lesion of pelvic and peripheral skeleton corresponding to brown tumors.